Hannah and her dad - Caisley, Raewyn (Thomas Nelson Melbourne, 1994)
Hannah and Her Dad is a heartwarming children's book that celebrates the special bond between a young girl named Hannah and her father. Through a series of everyday adventures and moments, the story highlights their playful interactions, shared experiences, and the love that strengthens their relationship. With charming illustrations and relatable scenarios, the book captures the joy of family time, encouraging children to appreciate the little things in life. This touching narrative reinforces themes of love, connection, and the importance of spending quality time with loved ones.